(untitled) (City: History, Culture, Society, 2017)
On April 12, 2016, at the Lviv Branch of the Institute of Ukrainian Archeography and Source Studies. MS Grushevsky hosted a joint meeting of the Seminar on Historical Urban Studies and the seminar “Cartography and History of Ukraine” of the Lviv Branch of the Institute of Ukrainian Archeography and Source Studies of NAS of Ukraine named after M. Hrushevsky. MS Hrushevskyi, which discussed the content of filling the future volume 3 of the Atlas of Ukrainian Historic Cities, dedicated to Zhovkva.